Polityka podatkowa środkowoeuropejskich krajów członkowskich Unii Europejskiej w warunkach harmonizacji podatkowej - Szczodrowski, Grzegorz (Tax Policy of the EU Member States from Central Europe in Conditions of Tax Harmonization, 2009)
The article concerns ways to increase tax competitiveness of the Central Europe's EU member states. In the first part, it characterizes the principle of tax harmonization, as a barrier of tax system changes. The second part presents the main changes that have taken place in the tax systems between 2004 and 2009 in these countries. Then the author describes the synthetic assessment of the effects of tax reform in the EU member states from Central Europe, according to two rankings: Index of Economic Freedom (Heritage Foundation and "The Wall Street Journal") and 2009 Paying Taxes (The World Bank and PriceWaterhouseCoopers.)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 324-331